The social function of educational guidance: Challenges and perspectives - Rocha, Aline Barros da (Seven Editora, 2023)
The general objective of the research was to study the role of the educational advisor in the current school, and in a specific way: to present the educational practice of school guidance, as well as to point out the perspectives and challenges faced by the counselor in the daily life of the school. Thus, the problem that gave rise to the featured article was: Is the educational advisor the main or supporting actor in the school space? Thus, a precise analysis of the theoretical framework composed by Chalita (2005), Grinspum (2003), Lück (2001), Pimentel (2006), Urbanetz (2008), among others, was carried out to support and substantiate this work. With this framework, the development of the work was elaborated through an exploratory - qualitative approach.Coming to the conclusion, based on the context presented, that one of the challenges currently presented to this professional is to find support outside the school, to carry out the work of rescuing the student from the world of drugs, social and family violence, factors that influence the school environment. It is an arduous task, but not impossible for this education professional. DOI:https://doi.org/10.56238/sevened2023.006-020